The graphics coach - Murray, Katherine 1961- (Personal trainer series, 1992)
A guide to video cards, colour monitors and the many graphic file formats. Sample explanations on how to translate graphics to import or export into other applications. This package is designed to help users maximize the performance of their existing graphics equipment.